Immunotherapy in NSCLC Patients With Brain and Leptomeningeal Metastases - Pierret, Thomas; Giaj-Levra, Niccolò; Toffart, Anne-Claire; Alongi, Filippo; Moro-Sibilot, Denis; Gobbini, Elisa (Frontiers in Oncology, 2022)
Immunotherapy has now integrated the treatment strategy for most patients with non-small cell lung cancer (NSCLC). However, pivotal clinical trials that demonstrated its impressive efficacy, often did not include patients with active, untreated brain metastases or leptomeningeal carcinomatosis. Nevertheless, NSCLC is the most common tumour to metastasize to the brain and patients develop brain and meningeal involvement in approximately 40% and 10% of cases respectively. Consequently, the appropriate care of these patients is a recurrent clinical concern. Although there are many aspects that would merit further investigation to explain the mechanism of intracranial response to immune checkpoint inhibitors (ICPs), some data suggest that they are able to cross the blood-brain barrier, resulting in local tumour microenvironment modification. This results in a similar clinical benefit in patients with stable, previously treated brain metastases compared to the general population. Despite important limitations, some real-life studies have described the ICPs efficacy maintained also in less selected patients with untreated or symptomatic brain metastases. In contrast, few data are available about patients with leptomeningeal carcinomatosis. Nevertheless, neurological complications due to ICP treatment in patients with brain metastases have to be evaluated and carefully monitored. Despite limited data are available in the literature, we purposed this review to shown the multimodal treatment of these patients with brain metastases and/or leptomeningeal disease should be discussed during the history of disease, participating in the local and possibly systemic control of NSCLC.